Efficient Pharmacokinetic Modeling Workflow With the MonolixSuite: A Case Study of Remifentanil - Pauline Traynard; Géraldine Ayral; Monika Twarogowska; Jonathan Chauvin (Wiley, 2020)
MonolixSuite is a software widely used for model‐based drug development. It contains interconnected applications for data visualization, noncompartmental analysis, nonlinear mixed effect modeling, and clinical trial simulations. Its main assets are ease of use via an interactive graphical interface, computation speed, and efficient parameter estimation even for complex models. This tutorial presents a step‐by‐step pharmacokinetic (PK) modeling workflow using MonolixSuite, including how to visualize the data, set up a population PK model, estimate parameters, and diagnose and improve the model incrementally.